Study on factors affecting utilization of maternal health services among mothers having under 5 children in Tharu community of Hansposa VDC, Sunsari district. - Rai, Rabina (2014)
ABSTRACT: This study was carried out with the objective to generate the information on the status of utilization of maternal health services and factors affecting it, so that they can be used for program planning and implementation to increase utilization of maternal health services and decrease factors affecting it. A sample of 93 mothers having under five children of Hansposa VDC were face-to-face interviewed using semi-structured questionnaire. This was completely a non-experimental cross-sectional study and the sampling method was systematic random sampling. The data were analysed using univariate frequency table and chi-square for bivariate analysis. The study revealed that 55.9% of respondents belonged to (23-28) years of age group and 23.7% belonged to 29-35 years of age. Similarly, 65.6% respondents belonged to high economic status; and 48.4% were literate. Also, 69.9%, 83.9%, 92.5% of the respondents had inadequate knowledge about ANC services, Delivery services and PNC services respectively. Moreover, all of the respondents opined that maternal health care services were easily accessible and its provider was also easily available during ANC and delivery services. Whereas, regarding PNC services, 32.3% respondent opined that the services were easily accessible and the provider easily available. Similarly, almost all i.e.100% of the respondents utilized ANC services where as 35.5% utilized delivery services and 32.3% utilized PNC services. Bivariate analysis showed no significant association between age, knowledge about maternal health services, availability of maternal health care provider, accessibility of maternal health services and decision making power of respondent. The bivariate analysis revealed significant relationship only between education status and delivery services utilization; also between economic status and PNC services utilization Since, mothers who were educated and belonged to high economic status have significant relationship with utilization of delivery services and PNC services, the study recommended that mothers who were educated and belonged to high economic status should be made the target group while planning the awareness program regarding maternal health services utilization. Also, the health services utilization must be carried out regardless of the age, knowledge about maternal health services utilization, accessibility of maternal health services and availability of its provider program related to maternal